Penyuluhan Pentingnya Kesadaran Tentang Bahaya Merokok Terhadap Kesehatan Bagi Siswa SMA Negeri 4 Kota Kupang Nusa Tenggara Timur - Sigit Purnawan; Apris A. Adu; Agus Setyobudi; Muntasir Muntasir (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
One of the public health problems is smoking behavior that occurs in various circles of society in Indonesia, therefore it is necessary to conduct counseling to provide awareness of the dangers of smoking to health. This community service is carried out with the intention of students understanding the efforts to anticipate the calamity of smoking on health, also active for disseminate it to the family environment, learning environment, and society. The stages of community service are carried out by preparation, implementation, and evaluation activities. Furthermore, the acquisition of service activities is presented descriptively and narratively. The results of service activities are based on knowledge measurement through measurements before and after the activity. The measurement results before the participants' activities gave a score of 80.88% from 130 participants. There are 15 question points, the most incorrect responses are on questions related to the catastrophe of smoking, the content of cigarettes, health problems caused by smoking, the dangers or impacts of smoking behavior that can lead to lung cancer, smoking behavior in daily interactions to prevent disease. lung cancer, an activity that is useful for supporting physical health. After the presentation of the counseling material on the catastrophe of smoking on health, measurements were made after the activity to find out whether there was a transformation of students' knowledge after receiving lectures and counseling. The results of measuring the activity after the activity showed that the participants gave a score of 95.50% of the 130 participants. There is an increase in knowledge of 14.62%. The school must carry out further development in the field of public health on an ongoing basis so that students can be trained to become facilitators or health agents both at school and at their residence and also to increase the role of the school health business (UKS) in following up on various health problems that can be handled.